OPTIMATRIX v2.0: Optimised protocol to mitigate microbial blooms in the micro-Matrix bioreactor platform used as an ex vivo human distal colon model - Arghya Mukherjee; Nicola Ferremi Leali; Elisa Salvetti; Sandra Torriani; Paul D. Cotter; Harsh Mathur (MethodsX)
We previously reported optimisation of the methodology to mitigate Escherichia coli blooms and associated loss of microbial diversity when using the micro-Matrix bioreactor platform as an ex vivo model of the human distal colon. Here, we provide further critical insights that we have gained in this regard through follow-up experiments. We tested four separate faecal fermentation media compositions for the purposes of such ex vivo distal colon model experiments and found that the media composition described by MacFarlane et al. is the most suitable for mitigating such microbial blooms, and concurrently, maintaining microbial diversity. We also tested if pooled or individual donor faecal samples were more suitable and found that pooled samples performed better in terms of maintaining gut microbiota diversity in such batch culture model experiments using the micro-Matrix system. Finally, we determined that prolonged experiments, i.e. for durations of up to 96 h, may be warranted with a view to affording particularly fastidious gut microbes an opportunity to grow and compete with their less fastidious counterparts. Essentially, we provide critical insights into: • Optimal faecal fermentation media to minimise blooms and preserve diversity in ex vivo colon model experiments • Optimal faecal inoculum source and duration of experiments.